Job Satisfaction or Employee Engagement: Regardless of Which Comes First, Supportive Leadership Improves Them Both. Issue 4 (November 2022) - Prentice, Stephen B.
Problem: While the debate continues over which comes first, employee engagement or job satisfaction, there is no debate regarding the high positive correlation that exists between them, nor their impact on organizational performance and productivity, company reputation, customer satisfaction, and turnover intention. Yet, HRD and HRM practitioners have been remise in advancing current and relevant leadership theories resulting in deficiencies in leadership theory, training, and practice. Solution: Considering the importance of employee engagement and job satisfaction to the success and reputation of an organization, it is incumbent upon HRD and HRM practitioners to collaboratively research and evaluate current and relevant leadership theories, and based on the findings, develop strategies and interventions for improving leadership training. Stakeholders: Companies, corporations, learning institutions, and organizations of any nature would benefit from this knowledge as they develop training and educational interventions purposed to improve employees' work engagement and job satisfaction.